Media diversity and public deliberation in Egypt: the case study of Law 107 of year 2013 on organizing the right to public meetings, marches, and peaceful protests - El Basnaly, Dina Ahmed (AUC Knowledge Fountain, 2015)
This research aims to identify the extent to which ownership, workforce, demography, and viewpoints in Egyptian private satellite stations are diverse and whether the existing levels of media diversity lead to efficient televised public deliberation. The research samples “Al-Hayat TV"‚ “CBC Egypt", and “Al-Nahar TV", which are the television stations with the highest viewership in Egypt. Egypt's law 107 of year 2013 on organizing the right to public meetings, marches, and peaceful protests is chosen as a case study of a policy issue that is tackled through televised deliberations. In-depth interviews and qualitative content analysis are used to answer the research's main question and sub-questions. The results shows that Egyptian private stations are owned by multiple owners, but such multiplicity does not meet the complete criteria of ownership diversity. Demographic and viewpoint diversities are missing, while workforce in these stations is partially diverse. These levels of ownership, workforce, demographic, and viewpoint diversities hinder most of the components that shape televised public deliberation.